Potencialidad turistica del patrimonio geologico en el Parque Nacional - Ahumada, Ana Lia (2010)
In the west slope of Aconquija Range, prevail the mountain arid-semiarid climate. Between 3000 m AS and more than 5000 m AS occur freezing phenomena. Were identified cryogenic forms( rock glaciers and morenic complex) and peats. These geoforms regulate the hydric regime in the region. W e study the Río Chiflon basin. The objective is define the environmental conditions, the actual characteristics of the cryogenic geoforms and the high geoecological belts. The degradation of the reservoir-geoforms increase by Climate Change and improper management. The recommendation is to establish parameters of conservation and the consciousness to people.